Proceedings of the Ninth International Conference on Mathematics and Computing ICMC 2023 - Giri, Debasis; Gollmann, Dieter; Ponnusamy, S.; Kouichi, Sakurai; Stanimirović, Predrag S.; Sahoo, J. K. (Lecture Notes in Networks and Systems, 2023)
XXV, 428 p. 97 illus., 65 illus. in color.